Determinants of the economic reintegration in ex-combatants of the department of Bolívar, Colombia - Luna-Amador, Jorge; Padilla-Castilla, Amalfi; Escobar-Espinoza, Andres (Sociedad y Economía, 2020)
This article aims to determine the factors that influence the economic reintegration of ex-combatants of insurgent groups in the department of Bolívar, Colombia. To this end, some socio-economic variables were analyzed, such as age, educational level, gender, marital status, descent, family income, the former armed group and the type of demobilization of the individual. Methodologically, an econometric model of binary selection was applied. Among the main conclusions of this article, it is emphasized that the determinants of economic reintegration in the department of Bolívar are the educational level, gender and family income of the ex-combatants.